Effective Corporate Governance to Prevent Fraud in Public Sector in Indonesia - Ivan Gunawan (Asia Pacific Fraud Journal, 2019)
Fraud in public sector is still widespread in Indonesia. Good corporate governance and internal control can prevent fraud. This paper examine corporate governance in Indonesia. Corporate governance and prevention of fraud can affect the economy of a country. Proper law enforcement is needed to reduce fraud and corruption. Ethical culture and governmental structure is a factors to be considered to create a better institutional environment. Governmental internal control is need to be improved in order to prevent fraud. Internal Auditor can be more effective in preventing fraud than external auditor. The ACFE’s 2008 survey provides empirical evidence to this effect as the survey found that over 19% of the respondents’ fraud cases were initially detected by internal audits versus about 9% that were discovered by external audits.